RETRACTED: Analysis of The Influence of Perceptions of Price, Service Quality, and Promotions on Customer Satisfaction Users of Transportation Services (Bluebird Taxi) - Muthia Chania Devy; Herry Krisnandi; Kumba Digdowiseiso (Journal of Social Science, 2024)
This research was conducted to analyze the influence of price perception, service quality, and to perception to customer satisfaction of Bluebird taxi service user. Indicators used for price perception include perception of quality, perception of cost, perception of price difference, and reference price. Indicators used for service quality include tangibles, reliability, responsiveness, assurance, empathy. Indicators used promotions include promotional frequency, promotional quality, promotion quantity, promotion time, suitability of promotional goals. While the indicators used for customer satisfaction, always buy products/ service, will recommend to others, fulfillment of customer expectations after buying products/ services. The sample in this research are 100 people. The sampling technique in the research of collecting the sample method randomly using questionnaire. The analytical method used in this research is descriptive analysis method through perception level and inferential method using IBM SPSS 17 program. Linear regression equation that answer the influence of price, service quality, and promotion to customer satisfaction is Y = 1.622 + 195 X1 + 0.405 X2 + 0.251 X3. The results showed that the perception of price, service quality, and promotion directly have a positive and real effect on customer satisfaction.